THE BAR CODES AND THE TECHNOLOGY OF CARGO TRANSPORT SYSTEMS FOR PACKETS AND SMALL INDIVIDUAL PACKAGES IN THE CZECH REPUBLIC (Perner's Contacts, 2009)
The technology of the systems for intrastate cargo transport of packets and small individual packages is mentioned in the paper. The utilization of the bar (EAN) codes in these systems is described there next to it. The facts shown in the paper are based on the actual practices from the technologies used in these transport systems. The special attention is paid for high effectiveness of several points (and for better quality of operations and for results reached during the transport process). This technology is based on traditional chain: consignors – centers of consignors – transship point(s) – centers of consignees – consignee (it is known as the standard traffic system of type “door-to-door”).